Effect of using the active learning in the achievement of third grade intermediate students in mathematics and them tendency towards the study of its (Journal Of Educational and Psychological Researches, 2011)
Current research aims to find out:Effect of using the active learning in the achievement of third grade intermediate students in mathematics.Effect of using of active learning in the tendency towards the study of mathematics for students of third grade intermediate.In order to achieve the goals of the research, the researcher formulated the following two hypotheses null:There is no difference statistically significant at the level of significance (0.05) between two average of degrees to achievement the experimental group who are studying the use of active learning and the degrees of the control group students who study in the traditional method in mathematics.There is no difference statistically significant at the level of significance (0.05) between two average of degrees students the experimental group who are studying using the active learning and the degrees of the control group students who study in the traditional method in measurement of the tendency towards the study of mathematics.The research community consists of all the schools in the third grade students intermediate in the Maysan province, where the applied researcher experience. The researcher was selected randomly al-amani intermediate for boys and where there are three divisions of the third grade intermediate and was selected two divisions of which were distributed randomly into two groups, one experimental and the other control. The researcher equivalents between the two groups (experimental and control) In some variables such as (chronological age, previous average, achievement in mathematics, the degree of intelligence, educational level of parents).The Scientific content included the first four chapters (groups, relationships, and applications/ real numbers/ analysis/ mathematical sentences) of the book Mathematics for the third grade intermediate approved for the academic year 2010-2011.The researcher prepared two types of teaching plans, the first of the control group according to the traditional method, the second for the experimental group, who studied by the active learning strategies.  Has been prepared by the researcher to search tools are the achievement test and the measure of the tendency towards study of mathematics.The results of research had been, there is a statistically significant difference in achievement test and measure of the tendency towards study of  mathematics in favor of the experimental group.As a complement to research, the researcher formulated a number of recommendations and suggestions.